2019
DOI: 10.1111/ped.13728
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophilia and hyperamylasemia in patients with immediate food allergy

Abstract: BackgroundPresently, little is known about the laboratory data several hours after oral food challenge (OFC) in patients with immunoglobulin (Ig)E‐mediated immediate food allergy (FA).MethodsOne hundred and twelve subjects who underwent OFC at the present institute between 1 June 2016 and 31 March 2018, were enrolled in this study. Changes in laboratory data several hours after OFC were examined.Results OFC was positive in 76 patients and negative in 36. Increase in absolute neutrophil count (ANC) was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…However, no signi cant difference was found between hyperamylasemia and normal groups in AMC, monocyte percentage and serum creatinine preoperatively or postoperatively in this study. Additionally, previous studies [29,30]reported that hyperamylasemia was associated with the peripheral blood eosinophil level. Kimura et.al [30]found that there was a signi cant negative correlation between increase in serum amylase and decrease in AEC in oral food challenge-positive patients with immediate food allergy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, no signi cant difference was found between hyperamylasemia and normal groups in AMC, monocyte percentage and serum creatinine preoperatively or postoperatively in this study. Additionally, previous studies [29,30]reported that hyperamylasemia was associated with the peripheral blood eosinophil level. Kimura et.al [30]found that there was a signi cant negative correlation between increase in serum amylase and decrease in AEC in oral food challenge-positive patients with immediate food allergy.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, previous studies [29,30]reported that hyperamylasemia was associated with the peripheral blood eosinophil level. Kimura et.al [30]found that there was a signi cant negative correlation between increase in serum amylase and decrease in AEC in oral food challenge-positive patients with immediate food allergy. Weir et.al.…”
Section: Discussionmentioning
confidence: 93%
“…However, no significant difference was found between hyperamylasemia and normal groups in AMC, monocyte percentage and serum creatinine preoperatively or postoperatively in this study. Additionally, previous studies [ 31 , 32 ]reported that hyperamylasemia was associated with the peripheral blood eosinophil level. Kimura et al [ 32 ] found that there was a significant negative correlation between increase in serum amylase and decrease in AEC in oral food challenge-positive patients with immediate food allergy.…”
Section: Discussionmentioning
confidence: 94%
“…Значимое повышение уровня амилазы в крови происходит при пищевой аллергии. К такому выводу пришли японские исследователи, исследовав содержание амилазы в крови пациентов, страдавших IgE-опосредованной пищевой аллергией немедленного типа (n=120), после проведения перорального провокационного теста [29]. В подгруппе больных с положительными результатами провокационного теста у 33,3% пациентов зафиксировали значимое повышение уровня амилазы >100 Ед/л (медиана -642 Ед/л).…”
Section: патогенетические механизмыunclassified
“…В 5 случаях рост уровня амилазы крови сопровождался увеличением сывороточной концентрации липазы. Получив такие данные, М. Kimura et al предположили, что обнаружение МАЕ при пищевой аллергии может свидетельствовать о вовлечении ПЖ в патологический процесс: «ПЖ является органом-мишенью при пищевой аллергии немедленного типа» [29].…”
Section: патогенетические механизмыunclassified